An Introduction to GPS - Jorge R. Rey (EDIS, 2006)
ENY-728, a 7-page fact sheet by Jorge R. Rey, describes the history of the global positioning system (GPS), how it works, the uses for GPS, and receiver setup. Includes additional Web Resources. Published by the UF Department of Entomology and Nematology, April 2006. Also available in Spanish (ENY-728S, El Sistema de Posicionamiento Global - GPS).